PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI KANTOR CAMAT LOLOFITU MOI KABUPATEN NIAS BARAT - Ike Krisna Gulo (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The purpose of this research is to find out how big the influence of motivation and compensation is on the performance of employees at the Lolfitu Moi sub-district office, West Nias Regency. This research uses a quantitative type of research to see the relationship between variables and the object being studied in a more causal manner, so that in the research there are independent variables and dependent variables. The sampling technique in this research used total sampling with a sample size of 32 employees. Data collection uses questionnaires or questionnaires in data analysis techniques using multiple linear regression analysis. The results of this research show that motivation (X1) has a significant effect on employee performance (Y) where the motivation variable (X) obtained a value of tcount (3.646) > ttable (1.694) and a significance level of 0.001 < 0.05. Furthermore, the compensation variable (X2) has a significant effect on employee performance (Y) where the value of tcount (1.796) > ttable (1.694) and the significance level is 0.115 > 0.06, which means that partially the compensation variable (X2) has a significant effect on the performance variable. employee (Y). The results of the simultaneous test (F test), show that the value of Fcount (3.227) > Ftable (2.701) and the significance level is 0.054 > 0.05, so it can be stated that the motivation variable (X1) and compensation (X2) simultaneously have a positive and significant effect on the variable employee performance (Y). The coefficient of determination (R2) is 0.177, so it can be interpreted that motivation and compensation are only able to explain employee performance variables by 77% while the remaining 23% is not explained in this research.